Spiritual Well-Being May Buffer Psychological Distress in Patients With Implantable Cardioverter Defibrillators - Elena Salmoirago-Blotcher MD, PhD; Sybil Crawford PhD; Chau Tran BA; Robert Goldberg PhD; Lawrence Rosenthal MD, PhD; Ira Ockene MD (SAGE Publishing, 2012)
Psychological distress is common in patients with implantable cardioverter defibrillators and has been associated with a worse prognosis. The authors examined whether spiritual well-being is associated with reduced psychological distress in patients with ICDs. The Functional Assessment of Chronic Illness Therapy-Spiritual Wellbeing (FACIT-SWB) questionnare and the Hospital Anxiety and Depression Scale (HADS) were used to measure spiritual well-being and overall psychological distress. Multivariate linear regression was used to explore the relationship between these variables. The study sample included 46 implantable cardioverter defibrillator outpatients (32 males, 14 females; age range = 43-83 years). An inverse association between HADS and FACIT-SWB scores was found, persisting after adjustment for demographics, anxiety/depression, medications, therapist support, and functional status ( F = .001; β = −0.31, confidence interval = −0.44, −0.19). In conclusion, spiritual well-being was independently associated with lower psychological distress in ICD outpatients. Spiritual well-being could act as a protective factor against psychological distress in these high-risk patients.